THE INFLUENCE OF FOOD IMAGE ON TOURIST SATISFACTION AND WORD-OF-MOUTH INTENTION: THE CASE OF DALAT, LAM DONG PROVINCE, VIETNAM - Nguyen, Thi Thanh Ngan (Trường Đại học Đà Lạt, 2024)
Local food influences destination choice and enhances destination attractiveness. This study explores the links among food image, tourist satisfaction, and word-of-mouth (WOM) intention regarding local food in Dalat, Lam Dong Province, Vietnam. A quantitative method was applied to a sample of 327 domestic tourists chosen by convenience sampling. A model was proposed and then tested using confirmatory factor analysis and structural equation modeling. The results confirm the existence of significant relationships among food image, tourist satisfaction, and WOM intention. Tourist satisfaction is influenced by three significant dimensions of food image: food safety and health, restaurant service, and food taste and popularity. This study explores how restaurant service influences both tourist satisfaction and WOM intention. A negative relationship between food safety and health and WOM intention was found. Moreover, the results demonstrate that tourist satisfaction has a critical effect on WOM intention. The study also suggests some managerial implications for enhancing the use of local food and its image to encourage tourist satisfaction and WOM intention.